Genetic variation in GABRA2 moderates peer influence on externalizing behavior in adolescents. Issue 6 (13th October 2014) - Villafuerte, Sandra; Trucco, Elisa M.; Heitzeg, Mary M.; Burmeister, Margit; Zucker, Robert A.
Abstract Background Genetic predisposition and environmental influences are both important factors in the development of problematic behavior leading to substance use in adolescence. Involvement with delinquent peers also strongly predicts adolescent externalizing behavior. Several lines of evidence support a role of GABRA2 on externalizing behavior related to disinhibition. However, whether this genetic association is influenced by the environment such as peer behavior remains unknown. Methods We examined the moderating role of GABRA2 genetic variation on the socialization model of delinquent peer affiliation (at ages 12–14 years) on externalizing behavior (at ages 15–17 years) in the Michigan Longitudinal Study (MLS) adolescent sample. The sample consisted of 244 adolescents (75 females and 152 with at least one parent with a DSM‐IV lifetime alcohol dependence/abuse diagnosis). Peer delinquent activity reported by the participant and teacher‐reported adolescent externalizing behavior (Teacher Report Form (TRF) were assessed. Results No main effect of the GABRA2 SNP rs279826, which tags a large haplotype, on externalizing behavior was observed. However, there was a statistically reliable GABRA2 × peer delinquency interaction. The effect of peer delinquent involvement on externalizing scores and the rule breaking subscale is significantly stronger for those with the GG genotype compared to A‐carriers, whereas there was no effect of genotype on externalizing in the absence of peer delinquent involvement. No interaction was observed for the aggression subscale. Conclusion Our results suggest that the genetic effect of GABRA2 on externalizing behavior, more specifically on rule breaking is, at least in part, due to its effect on susceptibility to environmental exposure (i.e., peer delinquency).